B1 field comparison for RF coils in ultra‐high‐field MRI. Issue 25 (1st December 2013) - Yoo, H.; Lee, J.; Akgun, C.E.; Gopinath, A.; Vaughan, J.T.
Abstract : This reported work demonstrates the use of convex optimisation to localise the transverse magnetic B + 1 field in regions of interest for recently proposed multi‐sectioned alternating impedance coils and the traditional transmission line coil. An approach based on different axial slices to identical radio frequency (RF) coils except upper stripline structure is investigated. Electromagnetic simulation results are compared for RF coils and discussed in detail at 7.0 T.